Master Sergeant, Pusher, Midwife, or the Department Chair - Randall Bowden; Jesse Brock; Phillis Bunch (Academic Chairpersons Conference Proceedings, 2020)
Six decades of literature were examined to get a sense of the role of the academic chair. Three things emerge. Roles: (a) vary widely; (b) change drastically; (c) are culturally influenced. This session discusses the role’s development from the influence of societal changes more than duties assigned by administrators.
Keywords: Academic leadership; Department Chair; Roles & Responsibilities; Organizational Culture; Social trends; External factors